Performance based financing and job satisfaction in a semiurban health district in Cameroon - Jules Jules Owona Manga; André Arsène Bita Fouda; Lucien Mbida; Come Ebana Mvogo (AOSIS, 2018)
The performance based financing approach is being tested in four regions of Cameroon, including the Littoral region. Our study aimed to study the effects associated with the implementation of the performance based financing approach within the health facilities based in the health district of Edea in the Littoral region in Cameroon. We've carried out a crosssectional analytical study among 178 health personnel from 21 health facilities under PBF-contract within the health district of Edea. We have studied their sociodemographic characteristics, the individual and collective effects resulting from the performance based financing subsidies and the level of job satisfaction. Participants' job satisfaction was measured with the French version of the Minnesota satisfaction scale. The results were presented in a descriptive and analytical form at the alpha = 5% and the P-value 5%. We recruited 113 women and 65 men. The mean age was 39.19 ± 8.95 years. The individual results of the performance based financing were the regular collection of subsidies between F CFA 20-40.000 (42.1%), the improvement of working conditions (74.2%) and living conditions (67.4%) and the acquisition of new skills (69.7%). Collectively, participants confirmed the increase of the users attendance (65.7%), the improvement of the internal organization (79.8%), the purchase of new equipment (84.3%) and the improved quality of health care (86%). Satisfaction is influenced by age (P=0.016), gender (P=0.01), occupational category (P=0.04), type of health facility (P=0.02) and the amount of subsidies (P=0.03). The healthcare personnel's were satisfied with the improvement of their social conditions (66.67%), working conditions (62.88%), the transparency in health centers management (69%) and their involvement in the health centers' functioning (76.6%). Participants were dissatisfied with their salaries (70.2%) and the lack of opportunities for advancement (47.8%). The positive effects of the performance based financing approach contributed to the job satisfaction of the healthcare workers in the Edea health district. These results should prompt the government to extend the performance based financing approach to communities and other health districts in Cameroon.